2017
DOI: 10.1371/journal.pgen.1006628
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide pools dictate the identity and frequency of ribonucleotide incorporation in mitochondrial DNA

Abstract: Previous work has demonstrated the presence of ribonucleotides in human mitochondrial DNA (mtDNA) and in the present study we use a genome-wide approach to precisely map the location of these. We find that ribonucleotides are distributed evenly between the heavy- and light-strand of mtDNA. The relative levels of incorporated ribonucleotides reflect that DNA polymerase γ discriminates the four ribonucleotides differentially during DNA synthesis. The observed pattern is also dependent on the mitochondrial deoxyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 57 publications
8
104
0
2
Order By: Relevance
“…The persistent rNMPs found in mtDNA are therefore not due to unusually poor discrimination against rNTPs by the mtDNA polymerase. As has been found for many other DNA polymerases, the exonuclease activity of Pol ɣ does not contribute to rNMP removal .…”
Section: Ribonucleotides Are Incorporated During Mtdna Replication Ansupporting
confidence: 65%
See 2 more Smart Citations
“…The persistent rNMPs found in mtDNA are therefore not due to unusually poor discrimination against rNTPs by the mtDNA polymerase. As has been found for many other DNA polymerases, the exonuclease activity of Pol ɣ does not contribute to rNMP removal .…”
Section: Ribonucleotides Are Incorporated During Mtdna Replication Ansupporting
confidence: 65%
“…The rNMPs found in mature mtDNA are therefore not related to the lengthy RNA species that temporarily coat the displaced H-strand in the RITOLS model nor are they longer RNA primers left unremoved after replication initiation. The estimated number of rNMPs per double-stranded mtDNA molecule ranges from 36 and 54 rNMPs in cultured HeLa and primary fibroblast cell lines, respectively [9], to 65 rNMPs in mouse liver [8]. In accordance with these numbers, Moss et al [65] reported a higher frequency of rNMPs in solid tissues than in cultured cell lines.…”
Section: Features Of Mtdna and Its Replicationmentioning
confidence: 87%
See 1 more Smart Citation
“…Southern blotting followed by probe hybridization has been a steadfast tool to study restriction fragment length polymorphisms and detect rearrangements in immunoglobulin and T cell receptor genes (Current Protocols article: Brown, ). Southern blotting is one of the best‐described methods for analyzing human mtDNA maintenance (Berglund et al., ; Chen & Cheng, ; Hayashi et al., ; Holt et al., ; Kaukonen et al., ; Kornblum et al., ; Lamantea et al., ; Lehtinen et al., ; Luoma et al., ; Moraes et al., , ; Moretton et al., ; Peeva et al., ; Rocher et al., ; Ronchi et al., ; Schon et al., ; Shokolenko et al., ; Song et al., ; Tengan & Moraes, ; Wallace et al., ). Skeletal muscle mtDNA deletions are associated with the mitochondrial disease progressive external ophthalmoplegia (PEO) and traditionally have been detected via Southern blot analyses (Kaukonen et al., ; Lamantea et al., ; Moraes et al., ; Moslemi, Melberg, Holme, & Oldfors, ).…”
Section: Commentarymentioning
confidence: 99%
“…Studies utilizing Southern blotting have proven to be powerful tools to assess mtDNA maintenance in human cell culture and patient samples (Berglund et al., ; Chen & Cheng, ; Hayashi, Takemitsu, Goto, & Nonaka, ; Holt, Dunbar, & Jacobs, ; Kaukonen et al., ; Kornblum et al., ; Lamantea et al., ; Lehtinen et al., ; Luoma et al., ; Moraes et al., ; Moraes, Atencio, Oca‐Cossio, & Diaz, ; Moretton et al., ; Peeva et al., ; Rocher et al., ; Ronchi et al., ; Schon, Naini, & Shanske, ; Shokolenko et al., ; Song, Wheeler, & Mathews, ; Tengan & Moraes, ; Wallace et al., ) as well as in model organisms such as mice and yeast (Griffiths, Doudican, Shadel, & Doetsch, ; Hance, Ekstrand, & Trifunovic, ; Milenkovic et al., ; Trifunovic et al., ; Tyynismaa et al., , ; Young, Theriault, Li, & Court, ). Here we describe a straightforward Southern blotting and nonradioactive probe hybridization method to estimate the quantity of mtDNA in human genomic DNA samples.…”
Section: Introductionmentioning
confidence: 99%